Human ALKBH6 Is Required for Maintenance of Genomic Stability and Promoting Cell Survival During Exposure of Alkylating Agents in Pancreatic Cancer - Zhao, Shengyuan; Devega, Rodan; Francois, Aaliyah; Kidane, Dawit (Frontiers in Genetics, 2021)
Alpha-ketoglutarate-dependent dioxygenase (ALKBH) is a DNA repair gene involved in repair of alkylating DNA damage. There are nine types of ALKBH (ALKBH1-8 and FTO) identified in humans. In particular, certain types of ALKBH enzymes are dioxygenases that directly reverse DNA methylation damage via transfer of a methyl group from the DNA adduct onto α-ketoglutarate and release of metabolic products including succinate and formaldehyde. Here, we tested whether ALKBH6 plays a significant role in preventing alkylating DNA damage and decreasing genomic instability in pancreatic cancer cells. Using an E. coli strain deficient with ALKB, we found that ALKBH6 complements ALKB deficiency and increases resistance after alkylating agent treatment. In particular, the loss of ALKBH6 in human pancreatic cancer cells increases alkylating agent induced DNA damage and significantly decreases cell survival. Furthermore, in-silico analysis from The Cancer Genome Atlas (TCGA) database suggests that overexpression of ALKBH6 provides better survival outcomes in patients with pancreatic cancer. Overall, our data suggest that ALKBH6 is required to maintain the integrity of genome and promote cell survival of pancreatic cancer cells.